Human milk fatty acids composition is affected by maternal age. (2nd January 2017) - Argov-Argaman, Nurit; Mandel, Dror; Lubetzky, Ronit; Hausman Kedem, Moran; Cohen, Bat-Chen; Berkovitz, Zipi; Reifen, Ram
Abstract: Human colostrums and transition milk were collected from women under the age of 37 years and women aged 37 years and older. Transition milk of the younger group had lower fat content and 10-fold higher concentrations of omega 6 FA, eicosadecanoic, and arachdonic acids. Gestational age affected the colostrum concentration of total fat and omega 3 and omega 6 FA composition only in the older group. We concluded that age may be a factor in the FA composition of human milk. This should be taken into account when planning diets for pregnant women of different ages.